Future developments in biosensors for field‐ready SARS‐CoV‐2 virus diagnostics. (19th October 2020) - Fani, Mona; Zandi, Milad; Soltani, Saber; Abbasi, Samaneh
Abstract: According to the evidence, the coronavirus disease 19 (COVID‐19) is caused by a zoonotic pathogen named respiratory syndrome coronavirus 2 (SARS‐CoV‐2). This virus can spread through personal contact, respiratory droplets, and also through airborne transmission. A rapid, low‐cost, and effective biosensor platform is essential to diagnose patients with COVID‐19 infection, predominantly the asymptomatic individuals, and prevent the spread of the SARS‐CoV‐2 via transmission routes. The objective of this review is to provide a comparative view among current diagnostic methods, focusing on recently suggested biosensors for the detection of SARS‐CoV2 in clinical samples. A capable SARS‐CoV‐2 biosensor can be designed by the holistic insights of various biosensor studies. Abstract : Schematic representation for various detection methods for COVID‐19 infection.